Penentuan Rute Distribusi Produk Tekstil dengan Pendekatan Capacitated Vehicle Routing Problem With Time Windows (CVRPTW) - Fadlyansyah Achmad Lutfizein; Hilyatun Nuha (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study was conducted to address the issue of textile product distribution at PT XYZ, which lacks optimal delivery routes, resulting in high mileage and long distribution times. The objective of this study is to determine the optimal distribution routes using the Capacitated Vehicle Routing Problem with Time Windows (CVRPTW) method. The study was conducted using customer demand data, vehicle capacity, distance matrix, travel time matrix, service time, and customer service time limits. A mathematical model was developed using the Mixed Integer Linear Programming (MILP) approach and simulated using Google Colab with the assistance of the Python programming language and the PuLP Solver software. The results show that the CVRPTW method is capable of generating a more optimal distribution route compared to the company’s existing route, with a reduction in total travel distance from 5,466 km to 3,155 km and a reduction in total distribution time from 4,755 minutes to 3,093 minutes. The results indicate that the application of CVRPTW can improve distribution efficiency by reducing travel distance and distribution time.